Evidence of fibril-like β-sheet structures in a neurotoxic amyloid intermediate of Alzheimer's β-amyloid - Chimon, Sandra; Shaibat, Medhat A; Jones, Christopher R; Calero, Diana C; Aizezi, Buzulagu; Ishii, Yoshitaka (Nature structural & molecular biology, 2007)
Diffusible subfibrillar aggregates of amyloid proteins are potent neurotoxins and primary suspects in amyloid diseases including Alzheimer's disease. Despite widespread interest, the molecular structures of the amyloid intermediates and the conformational conversions in amyloid misfolding are poorly understood. Here we present a molecular-level examination of sequence-specific secondary structures and supramolecular structures of a neurotoxic amyloid intermediate of the 40-residue β-amyloid (Aβ) peptide involved in Alzheimer's disease. Using solid-state NMR and electron microscopy, we show that, before fibrillization, natively unstructured monomeric Aβ is subject to large conformational changes into a spherical amyloid intermediate of 15–35 nm diameter, which has predominantly parallel β-sheet structures. Structural comparison with Aβ fibrils demonstrates that formation of this β-sheet intermediate ( I β ) largely defines conformational transitions in amyloid misfolding. Neurotoxicity assays on PC12 cells show that I β shows higher toxicity than the fibril, indicating that the β-sheet formation may trigger neurotoxicity.